2017
DOI: 10.1002/mp.12082
|View full text |Cite
|
Sign up to set email alerts
|

Improved intercostal HIFU ablation using a phased array transducer based on Fermat's spiral and Voronoi tessellation: A numerical evaluation

Abstract: VTFS transducers are expected to provide improvement for intercostal HIFU applications compared to currently available clinical transducers, as they reduce both the energy density in the pre-focal zone and the energy exposure of the ribs. These characteristics allow for increasing either the re-sonication rate or the treatment volume per sonication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The literature that exists regarding the acoustic attenuation of ribs reported a wide range of data. There are some articles that specified rib attenuation, but the information regarding their source or measuring method is unknown. The values reported vary from 12–25 dB/cm‐MHz.…”
Section: Methodsmentioning
confidence: 99%
“…The literature that exists regarding the acoustic attenuation of ribs reported a wide range of data. There are some articles that specified rib attenuation, but the information regarding their source or measuring method is unknown. The values reported vary from 12–25 dB/cm‐MHz.…”
Section: Methodsmentioning
confidence: 99%
“…Ramaekers et al. designed a Voronoi-tessellated transducer based on Fermat’s spiral, compared the device to currently available clinical transducers, and showed that this design reduces acoustic energy deposit on the ribs and the energy density in the pre-focal zone ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…It also remains to be established to which extent ultrasound can penetrate rib bone and how important it is to account for this phenomenon when modelling the propagation of ultrasound in the abdominal region. The ability to model the propagation of ultrasound through ribs and assess the importance of this relative to the case of locally reacting ribs [2] would be beneficial, particularly when studying the heat transfer mechanisms which lead to skin burns in HIFU patients [26]. There is therefore a requirement for resorting to multi-domain BEM to deal with the treatment planning complexities outlined above.…”
Section: Introductionmentioning
confidence: 99%